Innate Immune Evasion Strategies by Human Immunodeficiency Virus Type 1. (12th August 2013) - Guha, Debjani; Ayyavoo, Velpandi
Abstract : Host immune components play both beneficial and pathogenic roles in human immunodeficiency virus type 1 (HIV-1) infection. During the initial stage of viral infection, a complex network of innate immune factors are activated. For instance, the immune cells express a number of inflammatory proteins including cytokines, chemokines, and antiviral restriction factors. These factors, specifically, interferons (IFNs) play a crucial role in antiviral defense system by modulating the downstream signaling events, by inducing maturation of dendritic cells (DCs), and by activation of macrophages, natural killer (NK) cells, and B and T cells. However, HIV-1 has evolved to utilize a number of strategies to overcome the antiviral effects of the host innate immune system. This review discusses the pathways and strategies utilized by HIV-1 to establish latent and persistent infection by defeating host's innate defense system.